Taxonomic review of two fossil crocodylians from the Cenozoic of South America and its implications for the crocodylian fauna of the continent - Cidade, Giovanne M.; Fortier, Daniel; Rincón, Ascanio Daniel; Hsiou, Annie Schmaltz (Zootaxa, 2019)
The crocodylomorph fauna of the Cenozoic of South America is one of the richest and most diverse in the world. The most diverse group within that fauna is Alligatoroidea, with nearly all of its species belonging to the Caimaninae clade. Many of the fossil alligatoroid species from the Cenozoic of South America were proposed based on very incomplete remains, and as a result their validity requires revision. Two such species are Balanerodus logimus Langston, 1965, from the middle Miocene of Colombia and Peru, and Caiman venezuelensis Fortier & Rincón, 2012, from the Pliocene-Pleistocene of Venezuela. This study has performed a thorough review of the taxonomic status of these two alligatoroid species, concluding that B. logimus is a nomen dubium and that Ca. venezuelensis is a junior synonym of the extant species Ca. crocodilus. This review offers a significantly more accurate scenario for alligatoroid diversity in the Cenozoic of South America in different epochs such as the Miocene and Pleistocene. Additionally, the record of Ca. crocodilus from the Pleistocene of Venezuela is the first fossil record that can be assigned to this species.